Participatory computer simulation to support collective decision-making: Potential and limits of stakeholder involvement - Becu N. (2014)
System models in agriculture and natural resource management are usually developed by researchers to advise policy makers on the likely outcomes of alternative scenarios. Except for data collection, stakeholders-like farm households-are rarely involved in the research process. Companion modeling (ComMod) has been developed as a modeling approach to include various stakeholders in a continuous feedback loop between researchers and stakeholders. Whereas other ComMod approaches have used role playing games as an interface between researchers and stakeholders-assuming that stakeholders have difficulties understanding a computer model-this paper explores the potential of a participatory modeling approach in which stakeholders are directly confronted with the model by assessing its assumptions, interpreting simulation results, and suggesting scenarios. The approach is applied to two villages in a watershed in northern Thailand. One lowland village, populated by farmers of mostly Thai ethnic origin, depends partially on an upland village inhabited by farmers of Hmong ethnic origin for its water supply. Water scarcity has led to conflicts between these two villages in the past. In three rounds of participatory simulation sessions the potential of the ComMod model was tested. Our findings confirm that researchers face particular challenges in making local stakeholders understand the model as a reproduction of reality and not as reality itself. The idea of a scenario as a hypothetical situation was also difficult to convey. An ex-post analysis among participants showed that farmers who attended several sessions had a clear understanding of the model and one-third of the participants thought it useful to exchange points of view with the other community and to define new collective rules for water sharing. Applying ComMod in a context that is characterized by social tensions and power differentials, however, needs careful consideration of the potential implications on less powerful actors. © 2007 Elsevier Ltd. All rights reserved.